Pressure injury prevention measures in pediatric wards: nursing professionals' actions - Mayara Kelly Moura Ferreira; Francisca Elisângela Teixeira Lima; Mariana da Silva Diógenes; Sabrina de Souza Gurgel Florencio; Patrícia Rebouças Araújo; Paulo César de Almeida; Cristina Oliveira da Costa (Universidade Federal do Ceará, 2023)
Objective: to classify the quality of nursing care and analyze the association between professionals' characteristics and the implementation of preventive measures for pressure injuries in hospitalized children. Methods: this observational, cross-sectional study involved 235 nursing professionals. The Pressure Injury Prevention instrument comprised three domains with a total of 23 items: Preventive measures and early detection of pressure injuries (9 items), Pressure relief measures (8 items), and Assessment and reporting (6 items), analyzed using the Positivity Index for Quality of Care. Results: Most participants were females (98.7%), with a mean age of 38.83 ± 9.94 years, nursing technicians (57.4%), and had more than five years of experience (77.1%). Nursing care was predominantly inadequate across all three domains, with 82.6% of actions rated as poor. Significant associations were found between "participation in training courses" and "work-related exhaustion". There was a trend towards increased compliance with measurements among professionals aged 31-40. Conclusion: nursing care was predominantly poor and participation in training courses and the presence of exhaustion were associated with better adherence to preventive measures. Contributions to practice: the study highlights the pressing need for investments in professional training and the provision of necessary resources to support high-quality and safe nursing care.